Frozen sand mold multi-mode additive and subtractive in-situ composite manufacturing method
By employing gradient freezing sand mold preparation, multimodal additive manufacturing, and gradient thawing regeneration processes, combined with high-precision low-temperature subtractive processing, the problems of insufficient forming accuracy and low material utilization in traditional sand casting have been solved, enabling efficient and high-precision manufacturing of complex metal components.
Patent Information
- Application Number
- CN202511399850.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-28
- Publication Date
- 2025-12-16
AI Technical Summary
Traditional sand casting suffers from problems such as insufficient forming accuracy, low interfacial bonding strength, low material utilization, and long process cycle, making it difficult to meet the requirements of high precision and high efficiency, especially in the manufacture of complex metal components.
By employing gradient freezing sand mold preparation, multimodal in-situ additive manufacturing, and gradient thawing regeneration processes, combined with high-precision low-temperature subtractive processing and multimodal additive manufacturing technology, a high-strength ice crystal skeleton is formed. This skeleton is then used to achieve efficient manufacturing of complex metal components through methods such as laser cladding, magnetic field directional deposition, and hot pressing sintering.
It improves forming accuracy and interface bonding strength, shortens manufacturing cycle, increases material utilization, reduces energy consumption and cost, and realizes high-precision and high-efficiency manufacturing of complex metal components.
Smart Images

Figure CN121131670A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of additive and subtractive hybrid manufacturing and precision sand casting, and particularly relates to a hybrid manufacturing method and device based on frozen sand mold and multi-modal in-situ additive. BACKGROUND
[0002] In the rapid manufacturing of complex metal components (such as aircraft engine turbine blades and automobile cylinder integrated oil circuits), sand casting is still the mainstream process due to its strong material adaptability, low cost and other advantages. However, the traditional sand casting has the following technical bottlenecks: the forming precision is limited, and the demolding process of the binder solidified sand mold easily leads to rough surface of the mold cavity, which is difficult to meet the high-precision features such as air film cooling holes. It is difficult to manufacture complex structures, and the traditional sand shooting forming process cannot realize the flow channel or honeycomb sandwich structure with small curvature radius, and the splicing of the core easily causes casting defects, and the material utilization rate is low. The existing sand mold needs to be broken and recycled after the casting is demolded, and the sand regeneration rate is low. The additive and subtractive hybridity is poor: the subtractive machining and additive strengthening in the traditional process are implemented in steps, which leads to low interface bonding strength and prolongs the process cycle by more than 30%.
[0003] In view of the above problems, the existing technology attempts to introduce ice mold casting or 3D printed sand mold, and uses SLS selective laser sintering, but still has the following disadvantages: the pure water ice mold has low strength and cannot withstand the milling load; the 3D printed sand mold needs high-temperature sintering, which has high energy consumption and cannot realize in-situ additive strengthening; the existing frozen sand mold demolding process sometimes uses natural thawing, which leads to sand clumping and obvious decrease in flowability of regenerated sand. Therefore, it is urgent to develop an integrated hybrid manufacturing method combining frozen sand mold precision subtractive, multi-modal in-situ additive and green regeneration, so as to break through the precision, efficiency and material limitations of traditional sand casting and meet the high-performance manufacturing requirements of complex metal components. SUMMARY
[0004] To solve the above problems, the application discloses a frozen sand mold multi-modal additive and subtractive in-situ hybrid manufacturing method, which aims to solve the problems of insufficient forming precision, weak interface bonding and low material utilization rate caused by low ice sand matrix strength, poor additive and subtractive process synergy and difficult sand mold regeneration in traditional sand casting. Through the integration of gradient frozen sand mold preparation, high-precision low-temperature subtractive machining, multi-modal in-situ additive and gradient thawing regeneration process, efficient, high-precision and high-reliability manufacturing of complex metal components is realized.
[0005] The technical scheme adopted by the present application is as follows: a frozen sand mold multi-modal additive and subtractive in-situ hybrid manufacturing method, comprising the following steps: Step 1: Gradient frozen sand mold preparation: mix quartz sand, nano magnetic particles Fe3O4 and deionized water, and inject into a temperature control mold. Form an ice crystal network skeleton at-30℃ to-50℃ through gradient freezing process. The sand mold has low porosity and high compressive strength.
[0006] Step 2: High-precision low-temperature subtractive machining: Use a five-axis CNC machine tool to mill the frozen sand mold, use diamond-coated tools, dynamically cool the cutting area with low-temperature -50℃ nitrogen gas jet, control the processing environment temperature below -20℃, and combine with laser displacement sensor real-time detection of machining allowance to compensate for ice sand shrinkage deformation, and obtain a smooth surface precision cavity.
[0007] Step 3: Multi-modal in-situ additive: At least one combination of the following additive processes is performed on the surface of the subtractive cavity in turn: Laser cladding: A laser beam with a power of 500-2000W melts the ice crystals to form an intermediate bonding layer with a thickness of 0.05-0.2mm; Magnetic field directional deposition: Apply an alternating magnetic field of 0.5-2T to drive nano-magnetic particles to fill the ice crystal gap directionally and build a three-dimensional interlocking structure; Hot-pressing sintering: Under local pressure of 5-20MPa and temperature of 200-800℃, realize densification of the additive layer through infrared temperature measurement and pressure closed-loop feedback control.
[0008] Step 4: Gradient thawing and sand regeneration: Use gradient thawing process of steam pressure to melt ice layer, the steam jet direction is 30-60° with the normal direction of the sand mold surface, and the sand and the casting are separated by turbulent flow. Step 5: The recycled sand is low in moisture content after vibration screening and microwave drying, and is recycled after adding nano-magnetic particles, with significantly increased regeneration rate.
[0009] As a further design of the present scheme, the particle size of quartz sand in the sand mold material is 50-200μm, the nano-magnetic particle Fe3O4 has a particle size of 10-50nm and accounts for 5-15wt%, and the porosity of the ice crystal network skeleton after mixing is low.
[0010] As a further design of the present scheme, the gradient freezing control includes: both the surface freezing rate and the internal freezing rate are controllable, the freezing direction is layer by layer from the outer surface of the sand mold to the inside, and the layer thickness is 1-5mm.
[0011] As a further design of the present scheme, in the numerical control subtractive machining step: diamond-coated tools are used, the cutting depth is 0.1-0.5mm; integrate laser displacement sensor to detect machining allowance in real time, and compensate for ice sand shrinkage deformation through adaptive algorithm.
[0012] As a further design of the present scheme, the multi-modal additive includes at least one combination of the following: laser cladding and magnetic field deposition are performed simultaneously, the laser power is 800-1500W, and the magnetic field strength is 1-1.5T; hot-pressing sintering and magnetic field deposition are alternately implemented, the sintering temperature gradient is 200-500℃ / min, and the magnetic field frequency is 20-50Hz.
[0013] As a further design of the scheme, the laser cladding is locally heated on the non-metallic material by a high-energy laser beam, so that the ice crystals are instantaneously sublimated to form micro-channels, and the surface hydroxyl groups of the sand particles are activated to promote the chemical bonding between the non-metallic particles. The liquid water after the ice crystals are dissolved is re-frozen by rapid cooling to form a densified interface structure. The implementation parameters are matched as follows: laser power 800-1500 W, scanning speed 50-300 mm / min, and ice crystal overmelting is inhibited by a closed-loop temperature control system; ice crystal regulation: the laser heat source penetrates the ice-sand pores, and the ice crystals are rapidly re-frozen by a nitrogen jet at a low temperature of-30 DEG C after being dissolved, and the interface bonding strength is increased.
[0014] As a further design of the scheme, the magnetic field deposition utilizes an alternating magnetic field to drive the directional migration of non-metallic magnetic particles to the ice crystal gap, and through the synergistic effect of the magnetic field force and the ice crystal dissolution-refreezing process, a three-dimensional interlocking reinforced structure is formed. The liquid water released by the ice crystal dissolution serves as a temporary bonding phase, and after solidification, mechanical anchoring of the particles and the sand skeleton is achieved. The magnetic field parameters are as follows: pulse magnetic field frequency 20-50 Hz, magnetic field direction and ice crystal growth direction form an angle of 45-90 DEG, and the particle filling depth reaches 0.5-2 mm; particle orientation: the magnetic particles are arranged along the ice crystal channels under the action of the magnetic field gradient; low-temperature solidification: the deposited sand mold is kept at-20 DEG C for 30-120 s, and the ice crystals are recombined to form a continuous skeleton, and the porosity is reduced.
[0015] As a further design of the scheme, the hot-pressing sintering promotes the rearrangement of the sand particles after the ice crystals are dissolved by gradient heating at 200-500 DEG C / min and local pressure of 5-20 MPa, and the micro-channels generated by the vaporization of residual moisture are used to promote the diffusion and bonding of non-metallic particles, and the water vapor after the ice crystals are dissolved is removed by vacuum suction to avoid pore residue.
[0016] Temperature control: the infrared temperature measurement module monitors the sand mold temperature in real time, and the heating rate is dynamically matched with the ice crystal dissolution rate; pressure coordination: the pressure head dynamically compensates for the shrinkage of the sand mold, and the compensation amount is 0.01-0.05 mm, the pressure holding time is 30-60 s, and the interface porosity is reduced.
[0017] As a further design of the scheme, in the in-situ bonding control: the thickness of the intermediate bonding interface is 0.05-0.2 mm, and the microstructure is eutectic structure; the three-dimensional interlocking structure is filled, and the magnetic particles are arranged along the ice crystal gap with small angle deviation.
[0018] As a further design of the scheme, in the post-processing step: the vapor pressure of the gradient thawing separation is 0.1-0.5 MPa, and the interval thawing time difference between each partition is 30-120 s; the microwave drying power is 5-10 kW, and the moisture content of the sand after drying is low.
[0019] The beneficial effects of the present application are as follows: (1) Through gradient freezing, a stable "ice crystal skeleton" is prepared by precise temperature control + sand ratio, and the precision dynamic compensation of laser displacement sensor during subtractive processing is matched, which not only avoids sand deformation, but also offsets the micro-shrinkage during processing, so that the cavity precision is improved, the cooling channel error is reduced, and the demand for precise components is met.
[0020] (2) The laser cladding forms a ceramic layer with enhanced bonding force, the magnetic field drives the magnetic particles to fill and build a high-strength three-dimensional interlocking structure, and then the porosity is reduced through hot pressing sintering, so that the interface shear strength is improved, and the casting defect rate is greatly reduced. (3) The molding, processing, additive manufacturing and regeneration are integrated to reduce process conversion time; the low-temperature processing and regional temperature control are combined to accurately control energy consumption, avoid energy waste, shorten the manufacturing cycle, and reduce energy consumption; (4) The sand is gently peeled off by gradient steam to protect the integrity of the sand, and after screening and drying, only a small amount of nanoparticles needs to be supplemented for recycling, forming a closed loop, realizing the improvement of sand regeneration rate, the reduction of additive loss, the reduction of cost, and the reduction of industrial solid waste. BRIEF DESCRIPTION OF DRAWINGS
[0021] Figure 1 The frozen sand mold additive and subtractive in-situ composite manufacturing process described in the embodiment of the application is shown in the figure.
[0022] Figure 2 The frozen sand mold multi-modal additive and subtractive in-situ composite manufacturing method described in the embodiment of the application is shown in the figure.
[0023] Figure 3 The sand mold filling and prefabrication described in the embodiment of the application is shown in the figure.
[0024] Figure 4 The cooling channel milling described in the embodiment of the application is shown in the figure.
[0025] Figure 5 The multi-modal in-situ additive manufacturing described in the embodiment of the application is shown in the figure.
[0026] Figure 6 The gradient thawing and sand mold regeneration described in the embodiment of the application is shown in the figure.
[0027] Figure 7 The process of the embodiment of the application and the traditional process are compared in the figure. DETAILED DESCRIPTION
[0028] The present application will be further clarified by the following description and embodiments, which should be understood not to limit the scope of the present application. It should be noted that the terms "front", "back", "left", "right", "upper" and "lower" used in the following description refer to the directions in the drawings, and the terms "inner" and "outer" refer to the directions towards or away from the geometric center of a particular component.
[0029] Aerospace engine turbine blade manufacturing application case. The above process is demonstrated below in connection with the manufacture of a specific turbine blade, the flow being as shown in Figure 1 The following process is implemented, taking a bi-alloy turbine stator blade as an example. The blade alloy outside is ZL205A aluminum alloy, with a surface covered with a nickel-based high-temperature alloy layer and containing an internal cooling channel. Sand mold filling and preparation: according to the blade geometry, the blade geometry and internal cooling channel space are reserved in the sand mold cavity. Natural silica sand is mixed with water to prepare the sand mold, wherein the silica sand particle size is about 100 mesh (about 150 μm), and water is used as a binder, accounting for about 3% to 7% of the mass of the sand (preferably about 4% in this embodiment). After mixing the sand mold material, it is loaded into the forming machine cavity for cooling. A liquid nitrogen circulating immersion device can be used to achieve gradient cooling from the surface to the inside, as shown in Figure 2 Specifically, uniform low-temperature airflow is provided by a vortex generator to enable liquid nitrogen to fully infiltrate each part of the sand mold and circulate to remove heat, with the freezing process temperature gradually decreasing from 0°C to about -15°C (or even -20°C). As the temperature decreases, ice crystals form on the surface of the sand particles, forming a bridge that rapidly solidifies the surface layer (the solid layer thickness can be more than 0.5 mm), and the inner layer is slowly frozen to ensure the overall structure is dense. After gradient freezing, the sand mold presents a structure with gradually changing density from the outside to the inside, overcoming the problem of uneven forming of large-sized sand molds that are difficult to freeze in one piece, and avoiding the risk of cracking due to stress concentration.
[0030] Raw materials and proportions: high-purity silica sand is used as the main aggregate, with a particle size uniformly distributed in 100-200 mesh, 80-150 μm; the binder is pure water, with an addition amount of about 4% of the mass of the silica sand, which can be adjusted to 3% to 7% according to the rigidity requirements of the sand mold. To enhance the freezing strength, a small amount of clay and other additives can also be mixed in at a proportion of 5% or less. Freezing parameters: the freezing temperature is controlled between -10°C and -20°C.
[0031] Experiments show that when the pre-cooling temperature drops to -15°C, the thickness of the solid phase layer of the sand mold increases; the freezing time depends on the volume of the sand mold, and is generally completed within 10-60 minutes. By reasonably controlling the cooling rate, for example, 1°C / min, thermal stress concentration can be avoided.
[0032] As shown in Figure 3Gradient freezing strategy: The method of layer-by-layer freezing from outside to inside is adopted, and a dense ice shell with a thickness of 0.2-0.5mm is formed on the surface of the sand mold in the early stage, and then gradually spreads to the center to form a gradient structure. As shown in the figure, the sand mold of the application adopts zoned refrigeration, the surface layer and thin-walled part are rapidly cooled and frozen, and the thick part is kept slow cooling. This gradient freezing method not only improves the forming precision of the sand mold, but also ensures the strength gradient, which is beneficial to subsequent processing.
[0033] Cooling channel milling: The sand mold is subtractively processed on a low-temperature milling machine. First, the blade contour is processed, and then a 23mm diameter ball end mill is used to cut the cooling channel along the reserved notch at high speed. The typical cutting parameters are spindle speed 2500rpm, feed rate 30mm / min, cutting depth 0.3mm, each channel depth about 23mm, width about 2mm.
[0034] The temperature and vibration of the sand mold during processing are strictly monitored to ensure that the size accuracy of the notch is controlled within ±0.1mm. After processing, a frozen sand mold with accurate cooling channel shape is obtained. The frozen sand mold is processed by numerical control milling in a low-temperature environment to process the accurate blade shape and internal cooling channel structure. During processing, the sand mold is placed in a sealed low-temperature processing chamber, and low-temperature inert gas is continuously supplied.
[0035] Low-temperature milling significantly reduces the softening and local stress of the sand mold binder, thereby reducing the deformation during processing: research shows that low-temperature milling with a tool fluid temperature of-190℃~-10℃ can reduce the blade thin-walled deformation rate by more than 31% compared with normal temperature dry cutting, and the optimized deformation can be controlled within 0.04mm. During processing, hard alloy coated tools are used, and small depth multiple cutting is used to reduce vibration and heat accumulation. Typical cutting parameters are: spindle speed 1000-3000rpm, feed rate 20-50mm / min, single cutting depth 0.1-0.5mm, and cutting width is controlled within 50% of the tool diameter. In order to further ensure the forming accuracy, online deformation detection and compensation means can be used, such as using a non-contact measurement system to monitor the deformation of the sand mold in real time, and adjusting the tool path to compensate for the deviation. These measures together improve the shape accuracy and surface finish after processing, so that the geometric error of the processed sand mold can be controlled within ±0.05mm, which is significantly better than traditional high-temperature mold processing.
[0036] The cutting fluid is sprayed with liquid nitrogen to quickly remove the cutting heat. Typical process parameters: speed 3000 rpm, feed 30 mm / min, cutting depth 0.2 mm, cutting width about 1 mm. Deformation compensation: finite element simulation is performed before machining to predict the elastic deformation of the sand mold during cutting. Combined with actual machining data, the tool path can be adjusted in real time.
[0037] As shown in Figure 4 When the sand mold bending is simulated or measured, the corresponding shape compensation is added through the NC program to ensure that the final machining shape is consistent with the design. The above measures effectively reduce the dynamic deformation of the thin-walled sand mold.
[0038] Multi-modal in-situ additive manufacturing: This embodiment uses three complementary additive processes in sequence: laser thermal bonding, pulsed magnetic field assisted deposition, and thermal deposition. The specific process is as follows: laser thermal bonding uses a high-energy laser beam with a wavelength of 1064 nm to locally heat non-metallic materials, causing ice crystals to sublimate instantaneously and form microchannels, while activating the hydroxyl groups on the surface of the sand particles, promoting chemical bonding between non-metallic particles. The liquid water after ice crystal dissolution is re-frozen by rapid cooling to form a densified interface structure.
[0039] As shown in Figure 5 The implementation parameters are matched as shown: laser power 800-1500 W, spot diameter 0.2-0.5 mm, scanning speed 50-300 mm / min, and the over-melting of ice crystals is suppressed through a closed-loop temperature control system; ice crystal regulation: the laser heat source penetrates the ice-sand pores, the porosity is 15-25%, and the ice crystals are re-frozen rapidly by a -30°C low-temperature nitrogen jet after melting, and the interface bonding strength increases.
[0040] The magnetic field deposition uses an alternating magnetic field (1-1.5 T) to drive non-metallic magnetic particles to migrate directionally to the ice crystal gap, and through the synergistic effect of magnetic field force and ice crystal dissolution-re-freezing process, a three-dimensional interlocking reinforced structure is formed. The liquid water released by the dissolution of ice crystals serves as a temporary binder, and after solidification, it realizes the mechanical anchoring of the particles and the sand mold skeleton. Magnetic field parameters: pulsed magnetic field frequency 20-50 Hz, magnetic field direction at an angle of 45-90° with the ice crystal growth direction, particle filling depth up to 0.5-2 mm; particle orientation: magnetic particles with a particle size of 50-100 nm are arranged along the ice crystal channels under the action of the magnetic field gradient; low-temperature solidification: the deposited sand mold is kept at -20°C for 30-120 s, and the ice crystals recombine to form a continuous skeleton, reducing the porosity.
[0041] The hot-press sintering is promoted by gradient heating at 200-500 ℃ / min and local pressure of 5-20 MPa to rearrange the sand particles after ice crystal dissolution, and the micro-channels generated by the vaporization of residual moisture are used to promote the diffusion and bonding of non-metallic particles, so that the high densification interface is formed. The water vapor after ice crystal dissolution is removed by vacuum pumping to avoid pore residue. Figure 5 As shown in the temperature control: the infrared temperature measurement module monitors the sand mold temperature in real time, and the heating rate is dynamically matched with the ice crystal dissolution rate; pressure coordination: the pressure head dynamically compensates the shrinkage of the sand mold, the compensation amount is 0.01-0.05 mm, and the pressure holding time is 30-60 s.
[0042] Gradient thawing and sand mold regeneration. As shown in Figure 6 After the forming of the part is completed, the sand mold is thawed and the sand material is recovered. In practice, a gradient thawing method of segmented heating can be used: first, slowly heat the casting together with the sand mold to 0°C in a low-temperature room, and then transfer it to a room temperature environment or warm water to gradually melt the ice, so that the surface and the inside are thawed synchronously. The heating rate is controlled to be within 1°C / min to prevent the casting from deforming due to rapid thermal expansion. As the ice crystals melt, the sand particles fall off loosely, and the sand mold collapses by itself, without the need for mechanical knocking. After thawing, the casting takes shape and can be directly taken out. Since the binder is ice crystal bonding, there is no harmful gas emission during the thawing process, and the sand material is not contaminated by chemical binders. The recovered sand is separated by a vibrating screen or air classification, and after the impurities and dust are removed, it is dried at 105°C for 1-2 h and can be recycled.
[0043] Thawing method: as shown in Figure 6 After the casting is demolded, it is first thawed at -10°C to 0°C to melt the surface of the sand mold, and then thawed at room temperature; for large parts, hot air or warm water can be used to accelerate ice melting without causing local overheating. The entire thawing process usually lasts for several minutes to tens of minutes.
[0044] Recovery efficiency: as shown in Figure 6 The frozen sand mold only contains ice binder and no organic components, and the sand particles can be directly separated after thawing. Through screening and drying, the recycling rate can be improved, and there is no need for chemical dissolution treatment of the sand particles, realizing environmentally friendly and efficient regeneration. Regeneration treatment: the recovered sand material is first removed of large ice blocks and impurities using a vibrating screen, and then dried at 100°C or above in an oven to restore the original particle size distribution.
[0045] Forming cycle: as shown in Figure 7As shown, the whole process cycle includes freezing the sand mold for about 30 min, low-temperature milling for about 23 h, laser thermal bonding for about 3 h, multi-layer superposition and cooling, thermal deposition for about 1 h, thawing and taking out for about 0.1 h, and the total time is about 68 h. Compared with the traditional casting process and precision casting, the manufacturing cycle is greatly shortened. The turbine blade obtained by the process of the application has high dimensional accuracy, the bonding strength of the inner and outer walls of the sand mold is better than that of conventional bonded castings, and the sand recycling rate is high.
[0046] In summary, the present application realizes high precision and high efficiency of turbine blade manufacturing through the gradient freezing sand mold and the synergistic process of low-temperature subtractive, multi-modal additive, gradient thawing regeneration, etc. The innovative point of using ice crystals as a binder not only improves the casting quality and interface bonding strength, but also significantly shortens the manufacturing cycle and improves the sand mold recycling rate, providing a green and efficient new technology for the manufacturing of aero-engine parts.
[0047] The technical means disclosed in the present application scheme are not limited to the technical means disclosed in the above-mentioned embodiments, and also include technical solutions composed of any combination of the above technical features.
Claims
1. A method for in-situ composite manufacturing of multimodal additive and subtractive materials using frozen sand molds, characterized in that, Includes the following steps: S1: Preparation of frozen sand mold: After mixing the sand mold material with water, an ice crystal network skeleton is formed by gradient freezing. The sand mold material contains 70-90 wt% quartz sand, 5-15 wt% Fe3O4 nanomagnetic particles with a particle size of 10-50 nm, and 5-15 wt% water. The freezing temperature is -30℃ to -50℃. S2: CNC subtractive machining: Precision milling of frozen sand molds is performed using a five-axis linkage CNC machine. The tool speed is 20,000-40,000 rpm, the machining environment temperature is ≤-20℃, and the surface roughness is controlled to Ra0.8μm. S3: Multimodal additive manufacturing: In-situ additive manufacturing is performed on the surface of the cavity after subtractive processing, based on at least one of laser cladding, magnetic field deposition, or hot pressing sintering, wherein: the laser cladding power is 500-2000W, and the spot diameter is 0.1-0.5mm; the magnetic field deposition intensity is 0.5-2T, and the frequency is 10-100Hz; the hot pressing sintering temperature is 200-800℃, and the pressure is 5-20MPa. S4: In-situ bonding control: By adjusting the temperature gradient of the heat-affected zone to 100-300℃ / mm or by magnetic field directional filling, the additive layer and sand-type ice crystals can be crystallized and bonded together or a three-dimensional interlocking structure can be achieved. S5: Post-processing: A gradient thawing and separation process is adopted, in which the ice layer is melted by steam at 30-50℃ in sections, and the sand is recovered by cyclone separation and microwave drying.
2. The method for in-situ composite manufacturing of multimodal additive and subtractive materials using a frozen sand mold according to claim 1, characterized in that, The quartz sand in the sand-shaped material has a particle size of 50-200μm, the nanomagnetic particles have a particle size of 10-50nm, and the porosity of the mixed ice crystal network skeleton is 20-40%.
3. The in-situ composite manufacturing method for multimodal additive and subtractive materials using cryogenic sand molds according to claim 1, characterized in that, The gradient freezing control includes: a surface freezing rate of 8-12℃ / min and an internal freezing rate of 1-3℃ / min; the freezing direction is to advance layer by layer from the outer surface of the sand mold inward, with a layer thickness of 1-5mm.
4. The in-situ composite manufacturing method for multimodal additive and subtractive materials using frozen sand molds according to claim 1, characterized in that, In the CNC subtractive machining step: diamond-coated tools are used with a cutting depth of 0.1-0.5mm; an integrated laser displacement sensor is used to detect the machining allowance in real time, and an adaptive algorithm is used to compensate for the shrinkage deformation of the ice sand with a compensation accuracy of ±5μm.
5. The in-situ composite manufacturing method for multimodal additive and subtractive materials using frozen sand molds according to claim 1, characterized in that, The multimodal additive manufacturing includes at least one of the following combinations: simultaneous laser cladding and magnetic field deposition, with a laser power of 800-1500W and a magnetic field strength of 1-1.5T; alternating hot pressing sintering and magnetic field deposition, with a sintering temperature gradient of 200-500℃ / min and a magnetic field frequency of 20-50Hz.
6. The in-situ composite manufacturing method for multimodal additive and subtractive materials using frozen sand molds according to claim 1, characterized in that, The laser cladding process uses a high-energy laser beam to locally heat non-metallic materials, causing ice crystals to sublimate instantaneously and form microchannels. At the same time, it activates hydroxyl groups on the surface of sand particles, promoting chemical bonding between non-metallic particles. The liquid water after the ice crystals dissolve is rapidly cooled and re-frozen to form a dense interface structure.
7. The in-situ composite manufacturing method for multimodal additive and subtractive materials using frozen sand molds according to claim 1, characterized in that, The hot-pressing sintering process involves gradient heating of 200-500℃ / min and local pressure of 5-20MPa to promote the rearrangement of sand particles after the ice crystals have dissolved. The microchannels generated by the vaporization of residual moisture promote the diffusion and bonding of non-metallic particles, forming a highly dense interface. The water vapor after the ice crystals have dissolved is removed by vacuum suction to avoid pore residue.
8. The in-situ composite manufacturing method for multimodal additive and subtractive materials using frozen sand molds according to claim 1, characterized in that, In the in-situ bonding control: the bonding interface thickness is 0.05-0.2 mm, the microstructure is a eutectic structure; the filling rate of the three-dimensional interlocking structure is 85-98%, and the directional arrangement angle deviation of magnetic particles along the ice crystal gaps is ≤5°.
9. The in-situ composite manufacturing method for multimodal additive and subtractive materials using frozen sand molds according to claim 1, characterized in that, In the post-processing steps: the steam pressure for gradient thawing and separation is 0.1-0.5 MPa, the thawing time difference between each zone is 30-120 s; the microwave drying power is 5-10 kW, and the moisture content of the dried sand is ≤0.5%.